Enjeux et limites de la professionnalisation d'un groupe « minoritaire » : les éducatrices de jeunes enfants (EJE) - Mej Hilbold
In a working environment which is almost entirely composed by women, minoritized, without visibility, early childhood professions have to struggle against representations of a women's work, « naturally» exercised by women, as if their skills arose from the private sphere (function of mothering). Their historical weapon against these representations is their "professionalization" -a professionalization thought here as a process of subjectivation-, which, today, for some categories, such as early childhood educators, requires a team management training. Should the normalization be an obligatory step for raising the profile of the professions? How can this profession become altered by the temptation of majority? This article is based on empirical data collected from collective nursery employees, students and teachers in training center for early childhood educators (ethnographic observations and non-directive interviews) and is characterised, at the theoretical level, by the critical review of the sociology of educational professions, in the light of gender studies.